2016
DOI: 10.1039/c5nj02123e
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite nanoparticles (HAP NPs): a green and efficient heterogeneous catalyst for three-component one-pot synthesis of 2,3-dihydroquinazolin-4(1H)-one derivatives in aqueous media

Abstract: HAP NPs were applied as a green heterogeneous catalyst for synthesis of 2,3-dihydroquinazolin-4(1H)-one derivatives. The nanocatalyst was prepared and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 64 publications
0
14
0
1
Order By: Relevance
“…We also observed that 4-pyrazoloaniline [32] which synthesized for prepare of our newly desired 2,3-dihydroquinazolin-4(1H)-one was well tolerated under our reaction conditions with 95% isolated yield (4o). [33], the possible mechanism for the synthesis of 2,3-dihydroquinazolin-4(1H)-ones from the three-component condensation of isatoic anhydride (1), aromatic amines (2), and aromatic aldehydes (4) in the presence of KCC-1/Pr-SO 3 H has been shown in Scheme 3. As can be seen, at first stage the acidic sites of the catalyst activated the carbonyl group of isatoic anhydride.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that 4-pyrazoloaniline [32] which synthesized for prepare of our newly desired 2,3-dihydroquinazolin-4(1H)-one was well tolerated under our reaction conditions with 95% isolated yield (4o). [33], the possible mechanism for the synthesis of 2,3-dihydroquinazolin-4(1H)-ones from the three-component condensation of isatoic anhydride (1), aromatic amines (2), and aromatic aldehydes (4) in the presence of KCC-1/Pr-SO 3 H has been shown in Scheme 3. As can be seen, at first stage the acidic sites of the catalyst activated the carbonyl group of isatoic anhydride.…”
Section: Resultsmentioning
confidence: 99%
“…4) [35,45 ~ 48] .该方法是由靛红酸酐合成 2,3-二氢喹啉- [35,45~48] . 图式 靛红酸酐与胺、醛/酮分步反应 Scheme 8 Stepwise reaction of isatoic anhydrides with amines and aldehydes/ketones "一锅法"的三组分串联反应生成 2,3-二氢喹啉-4(1H)-酮的机理如 Scheme 9 所示 [35,46,47] .首先, 靛红酸 [49,50] ; 无溶剂条件下, 该反应各原料在 NaOH 存在下在研钵中研磨均匀后再 转移入反应瓶中加热反应 30 min, 即可以 80%~96%的 收率得到目标产物(Eq. 5) [51] .…”
Section: 当末端炔烃参与反应时 所用的催化剂为 Ph 3 Pau-unclassified
“…Hydroxyapatite, one of the most important inorganic biomaterials, has extensive applications in drug delivery systems, bone grafts, catalysts and adsorbents because of its high specific surface area, low water solubility, availability, low cost and high stability.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, green chemistry is a term given to 12 principles, and following these principles makes a process and its reactions environmentally friendly and healthy performing, reduces the risk of toxic substances, lowers energy consumption, and enhances the efficiency up to a maximum. [11][12][13] Hydroxyapatite, one of the most important inorganic biomaterials, has extensive applications in drug delivery systems, [14] bone grafts, [15,16] catalysts [17] and adsorbents [18] because of its high specific surface area, low water solubility, availability, low cost and high stability.…”
mentioning
confidence: 99%